New phase within the SrO–RЕ2O3–GeO2 (RЕ = Dy–Lu) systems: Synthesis and quantum-chemical modeling. (March 2020) - Melkozerova, Marina A.; Enyashin, Andrey N.; Chufarov, Alexander Yu.; Baklanova, Yana V.; Tyutyunnik, Alexander P.; Zubkov, Vladimir G.
Abstract: The phase formation of Sr3 RЕ 2 (Ge3 O9 )2 ( RE  = Dy, Ho, Er, Tm, Yb, Lu) cyclogermanates was studied at 1000 and 1100 °C in air. It was shown that these compounds did not exist under these conditions, in contrast to cyclogermanates with large RE 3+ ions, such as La, Pr, Nd, Sm, Eu and Gd. Using the thulium-based system SrO–Tm2 O3 –GeO2 as an example, it was established that compounds with Sr/ RE atomic ratio other than 3/2 were formed instead of the expected Sr3 RЕ 2 (Ge3 O9 )2 . Single phase Sr4 TmGe5.667 O16.834 was prepared and characterized by X-ray powder diffraction. The quantum-chemical calculations confirmed the thermodynamic instability of strontium germanates Sr3 RЕ 2 (Ge3 O9 )2 with RE 3+ cations smaller than Gd 3+ . It is suggested that the prototypic structure of mixed strontium and Dy, Ho, Er, Tm, Yb and Lu rare earth germanates stems from the crystal structure of walstromite BaCa2 Si3 O9 . Highlights: The Sr3 RЕ 2 (Ge3 O9 )2 cyclogermanates with RE 3+ ions of small radii are unstable. The new phase Sr4 TmGe5.667 O16.834 was obtained by citrate method. DFT calculations reveal a structural relation of the new phase to walstromite.